Manchester triage in acute pulmonary embolism: can it unmask the grand impersonator?. Issue 12 (20th December 2011) - Paiva, L; Providencia, R; Faustino, A; Barra, S; Botelho, A; Leitao-Marques, A M
Abstract : Background: Acute pulmonary embolism (PE) is associated with high mortality risk. Early diagnosis is difficult because of non-specific clinical presentation and delay in imaging confirmation. Manchester Triage (MT) prioritises patients on the basis of illness severity and potentially recognises those with higher mortality risk. No studies of the role and impact of MT on rapid PE diagnosis and in-hospital mortality (IHM) have been carried out. Objective: To assess the appropriateness of MT in this set of patients presenting acutely to the emergency department (ED), and to determine whether it assists in a rapid diagnosis, acts as a protective triage tool and affects short-term mortality. Methods: Single-centre retrospective study of 176 consecutive patients with PE, assessed by MT in the ED between January 2006 and October 2010 (mean age 70.5±15.7 years, 38.6% men). The primary outcome measure was all-cause IHM. Results: IHM was seen in 30 (17%) patients. More than half of the patients with PE (54%) were classified as target time for first medical observation (MOb) ≤10 min. 73.3% of IHM occurred in this group (p=0.020) with several increased markers of illness severity. MOb ≤10 min was not associated with faster PE imaging confirmation. The average door-to-diagnosis time (PEDx) was 26.8±36.8 h and PEDx >17.0 h was associated with higher IHM (p=0.017). On multivariate analysis, thrombolysis and MOb ≤10 min were included in an IHM predictor model. Conclusion: MT has high sensitivity in identifying patients with PE at risk. Those patients assigned as MOb ≤10 min have increased markers of illness severity and higher IHM. MT acts as a protective system in this challenging set and should be used as a patient's first assessment, aiding the emergency medical team to recognise those in need of urgent assessment and treatment.